Practical difficulties in the management of hepatitis B in the Asia-Pacific region - Mohamed, R.; Desmond, P.; Suh, Dong-Jin; Amarapurkar, D.; Gane, E.; Guangbi, Y.; Hou, Jin-Lin; Jafri, W.; Lai, C.L.; Lee, Chang-Hong; Lee, Shou-Dong; Lim, S.G.; et al. (Blackwell Publishing, 2004)
The Asia-Pacific Expert Committee on Hepatitis B Management recently reviewed the impact of hepatitis B in the region and assessed the differences and similarities observed in the practical management of the disease in individual Asia-Pacific countries. Hepatitis B is a major health concern in the Asia-Pacific region, and of all chronically infected carriers worldwide, approximately 75% are found in Asia. The disease poses a considerable burden on healthcare systems, and is likely to remain a cause of substantial morbidity and mortality for several decades. Disease prevention activities, including screening and vaccination programs, have been implemented successfully in some Asia-Pacific countries and similar measures are being established in other parts of the region. The management of hepatitis B in the Asia-Pacific varies throughout the region, with each country confronting different issues related to treatment options, disease monitoring and duration of therapy. The influence of cost, availability of diagnostic equipment, and patient awareness and compliance are of additional concern. Although guidelines such as those developed by the Asian Pacific Association for the Study of the Liver have been created to address problems encountered in the management of hepatitis B, many physicians in the region still find it difficult to make satisfactory management decisions because of the treatment choices available. This article examines the different approaches to hepatitis B management in a number of Asia-Pacific countries, and highlights the difficulties that can arise when adhering to treatment guidelines and disease prevention solutions that have proved to be successful in the region.